2011
DOI: 10.4141/cjss2011-011
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessment of corn stover production for cellulosic ethanol in Quebec

Abstract: Whitman, T., Yanni, S.F. and Whalen, J.K. 2011.Life cycle assessment of corn stover production for cellulosic ethanol in Quebec. Can. J. Soil Sci.91: 997–1012. The province of Quebec has a target of 5% ethanol (EtOH) content in fuel by 2012, which means the province will require about 400 million L of ethanol per year based on current consumption. Current research is focused on “second generation biofuels” such as cellulosic EtOH, which can be produced from agricultural by-products like corn stover. A life cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 40 publications
0
16
1
Order By: Relevance
“…Once the corn stover left the feedstock production portion of the system, two different coproduct treatment methods, mass allocation and sub-division, were applied in GaBi to all feedstock production inputs in order to generate results for impacts due only to corn stover. Of the more commonly used co-product treatment methods, mass allocation typically attributes the most environmental burden to stover while sub-division attributes the least [21][22][23]. The mass allocation factor for stover in this study was 33 %, and it was applied to production inputs as well as EPIC modeling data input.…”
Section: Methodsmentioning
confidence: 99%
“…Once the corn stover left the feedstock production portion of the system, two different coproduct treatment methods, mass allocation and sub-division, were applied in GaBi to all feedstock production inputs in order to generate results for impacts due only to corn stover. Of the more commonly used co-product treatment methods, mass allocation typically attributes the most environmental burden to stover while sub-division attributes the least [21][22][23]. The mass allocation factor for stover in this study was 33 %, and it was applied to production inputs as well as EPIC modeling data input.…”
Section: Methodsmentioning
confidence: 99%
“…Some case studies in the USA have reported an environmental GHG benefit of no-till maize-and stover maize-derived ethanol compared to gasoline-fueled vehicles by LCA analysis [26,27]. In the first case, the no-till adoption was estimated to sequester 377-681 kg C ha −1 year −1 while, in the second, no SOC variation was accounted for Whitman et al [28], conducting a life cycle assessment of corn stover production for cellulosic ethanol in Quebec, showing that soil Fig. 1 Total amount of dry matter annually available (Mt d.m.…”
Section: Discussionmentioning
confidence: 99%
“…However, Whittaker et al [28] remarked that the inclusion of SOC changes in LCA analysis may reduce GHG emission savings by 133 % if the effect of cereal straw removal is properly taken into account. In a recent paper, Liska et al [29] noted that life cycle emissions will probably exceed the US legislative mandate of 60 % reduction in GHG emissions compared with gasoline (under the next US biofuel targets), if 6 t ha −1 year −1 of maize stover will be removed over 5 to 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…A LCA was carried out by Whitman et al [13] to evaluate corn stover feedstock production for cellulosic EtOH production in three corn-producing regions in Quebec for energy and greenhouse gas (GHG) impacts. In this study, in-field processes such as corn stover production, collection, transport, soil organic carbon (SOC) loss, and N 2 O emissions, as well as background processes of herbicide, fertilizer, seed, and fuel production and transport were considered as the system boundaries.…”
Section: Introductionmentioning
confidence: 99%